Jesus and YHWH-texts in the synoptic gospels - Brazil, Scott (Library of New Testament studies, 2024)
Scott Brazil examines the frequent practice of applying Old Testament YHWH-texts to Jesus in the Synoptic Gospels. He argues that this YHWH-text phenomenon evidences a high Christology in the primitive church that traces back to Jesus himself. He thus finds in this Synoptic practice a stinging contradiction against the modern critical theory that a high Christology took many decades to develop in the early church and exists only in John among the canonical Gospels. Brazil surveys the Synoptic Gospels in canonical order, exegeting dozens of passages in which OT texts originally referring to YHWH are either clearly or most probably applied to Jesus. He observes the frequency, diversity, and ubiquity of the practice, as well as its wide range of OT source material and its parallel to the NT practice of applying OT messianic texts to Jesus. And from the data he offers several ramifications, including the early deliberate employment of YHWH-texts to Jesus, the likelihood that Jesus is the source of the practice, the high Christology of the Synoptics, and the redemptive-historical metanarrative that Jesus is the divine interpreter and central figure of the Jewish Scriptures. Ultimately, Brazil argues that understanding the prolific application of OT YHWH-texts to Jesus in the Synoptic Gospels cannot be neglected without truncating genuine NT Christology